ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TABUNGAN MASYARAKAT PADA PERBANKAN UMUM DI KALIMANTAN BARAT TAHUN 2000.1-2010.4 - B21108020, TITIN PRIHATINI (Jurnal Curvanomic, 2015)
This study aims to investigate the influence of interest rate, GDP, the money supply and inflation on society in west borneo. The data used are secondary data in the annual report Indonesian bank since 2000-2010. The method used is descriptive method. Before the data is tested in the test data that is held determinant coefficient test, F test and t test. The result showed that there is a positive influencebetween interest rates on savings. There is a positive influence between GDP againts savings. While inflation and the money supply no effect on savings. The next results of the regression analysis with the five variables showed significant results with R= 0.914570 between interest rates, GDP, inflation, the money supply to savings. Partially the result of the t test, the variable interest rate and GDP significantly affect the savings effect, the variable of money supply does not significantly affect savings. As well as inflation does not significantly affect the savings. Adjusted R-square value of 0.861 indicates that savings can be explained by the variables of 0.861 percent, while the rest is explained by other factors. Keywords : Public savings and general banking.